‘Politics of Friendship’ in the Context of Wider Europe: Implications for European Space-making - Roald Plug (Nordia Geographical Publications, 2007)
This paper is engaged with the form of international relations the EU deploys with regard to its neighbouring states at the Eastern and Southern borders. The EU is excluding the so-called ‘Ring of Friends’ from active political participation in its Self-structure and is in this process of exclusion making migrants part of the process of othering. It puts forward the argument that precisely by the act of naming the Neighbours ‘Friends’, EU-discourse is undeliberately creating a discursive space within its transboundary governance-structure that could lead to a re-negotiation of the politics of inclusion and exclusion itself. Once a politics based on the virtues of Friendship and Fraternity can be thought of as a mature element within the political realm, this will open up new possibilities for re-thinking inclusiveness and hybridisation of cultural identities in a ‘wider’ European space.